Dinamika Komunikasi Viral Dalam Kasus Kematian Nia Kurnia Sari Di Kabupaten Padang Pariaman - Rivana Izzati Syahra; Elva Ronaning Roem; Sarmiati Sarmiati (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2026)
This study focuses on the viral communication phenomenon that occurred following the death of Nia Kurnia Sari, a teenage fried food seller from Nagari Guguak, 2x11 Kayu Tanam District, Padang Pariaman Regency, West Sumatra. This tragedy sparked widespread public attention, both locally and nationally, and generated diverse social responses spread through social media and online media. The purpose of this study is to examine the dynamics of viral communication that developed around the case. The research approach used a qualitative method with a case study design. Data were collected through in-depth interviews, documentation, and content observation on various platforms such as Instagram, TikTok, Facebook, and online media. This study applies Emotional Contagion Theory to explain how expressions of sadness, anger, and sympathy shared on social media can spread widely and form a collective emotional resonance. This theory emphasizes that viral communication not only conveys information but also transmits emotions that influence people's collective perceptions and actions. The results show that viral communication, in this case, is formed through content that is full of emotion and able to arouse people's feelings, such as uploaded photos, narrative videos, and condolences spread on social media. Social media platforms served as a public space for expressing empathy, anger, and demands for justice for Nia Kurnia Sari. Public solidarity was even expressed through musical works created in response to the case.